MENINGKATKAN HASIL BELAJAR SENI TARI SISWA MENGGUNAKAN MEDIA AUDITIF DI SMP NEGERI 25 PADANG - Haryono Haryono; Fuji Astuti; Herlinda Mansyur (SENDRATASIK UNP, 2018)
Abstract The background of the research was low mastery of students towards a learning material that would cause the low accomplishment of the most dance learning outcomes of students. It had not reached the Minimum Completeness Criteria (KKM) in the class VIII.4 SMP Negeri 25 Padang. One of the factors that influence the low learning outcomes of students was the application of learning media that had not been able to demand the active role of students. Therefore it was necessary to do research by applying auditive media to see student dance learning outcomes. The type of this research was classroom action research. The subject in this study were students of class VIII.4 SMP Negeri 25 Padang registered in the 2017/2018 school year consisting of 32 students. In this study, the method of data collection was using the learning outcome test in the form of posttest at the end of each cycle and observation sheet. The data obtained were analyzed using the classical learning completeness formula. Based on the results of the study, it was found that there was an enhancement of students in each cycle. In the first cycle, the students who got the score of 70 and above (according to the success criteria of the action) were 20 (62.50%) and 12 students (37.50%) who still got the score below 70. For cycle II, the number of students who got score above 70 was increased to 25 people (81.25%) while students who got below 70 were decreased to 7 people (18.75%) which meant the learning outcomes f dance have been increased. Thus, it could be concluded that the application of auditive media could improve the students’ learning outcomes of dance at SMP Negeri 25 Padang. Keywords: Auditive Media, Students’ Learning Outcomes